Comparison of transcranial Doppler flow velocity and cerebral blood flow during focal ischemia in rabbits - Els, Thomas; Daffertshofer, Michael; Schröck, Helmut; Kuschinsky, Wolfgang; Hennerici, Michael G. (Ultrasound in medicine & biology, 1999)
The predictive value of transcranial Doppler (TCD) cerebral blood flow velocity (CBFV) measurements for cerebral blood flow (CBF) calculations in humans is still controversial, and experimental correlative studies are lacking. The aim of the present study was to validate TCD signals of CBFV during focal cerebral ischemia. Therefore, CBFV determined in the middle cerebral artery (MCA) was compared with values of CBF obtained from autoradiograms of ischemic brain areas. To determine CBFV, a transcranial Doppler ultrasound probe (TCD) adapted to small sample volumes was used in 9 rabbits. CBF was quantified after a final infusion of [14C]-iodoantipyrine in the same animals. For focal cerebral ischemia induction, two threads were flushed upward simultaneously into the internal carotid artery, resulting in a flow reduction in the ipsilateral MCA. After thread occlusion, mean systolic CBFV in the MCA decreased from 49 ± 9 cm/s to 22 ± 3 cm/s. CBF in the caudate nucleus was reduced (19 ± 8 mL/100 g/min) compared to the contralateral nonischemic side (52 ± 18 mL/100 g/min). The decrease in hemispheric CBF correlated well with the decrease in both mean systolic (r = 0.97) and diastolic (r = 0.94) CBFV in the MCA (p < 0.01). The decrease in CBFV determined by transcranial Doppler ultrasound in the MCA appears to reflect the reduction in CBF in the affected brain hemisphere and can be used as a quantitative in vivo parameter for tissue perfusion.